How do central banks write on financial stability? - Čihák, Martin (IMF working paper ;, 2006)
To showcase their increasing focus on financial stability, many central banks and other institutions have started publishing regular reports on financial stability. The paper presents a survey of the available financial stability reports, and proposes a framework for assessing such documents. It illustrates how the framework can be implemented, and uses the findings to identify prevalent practices, recent trends, and areas for improvement.